Utilization of Interactive Podcast-Based Instructional Design and It’s Impact on Listening Skills - Abidin, Zainal; Chamalah, Evi (Jurnal Basicedu, 2025)
Students’ limited listening comprehension skills are often attributed to monotonous teaching methods that lack variety. This study aims to explore the implementation of interactive podcast-based instructional design and its impact on students’ listening comprehension in language learning. A systematic literature review method was employed, sourcing data from reputable academic publications between 2020 and 2025. The findings reveal that interactive podcasts incorporating elements such as quizzes and reflective questions enhance students' engagement, focus, and understanding of audio-based material. In addition to improving listening skills, these podcasts contribute to a more enjoyable and meaningful learning experience. However, challenges such as unequal access to technology and varied student ability levels were also identified. Despite these obstacles, the evidence supports the effectiveness of interactive podcasts as a pedagogical tool in language education. In conclusion, the use of interactive podcasts offers valuable insights for developing more innovative and effective teaching strategies, particularly in enhancing students’ listening comprehension